2013
DOI: 10.1095/biolreprod.112.106062
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Cumulus Cells Protect Maturing Oocytes from Increased Fatty Acid Levels by Massive Intracellular Lipid Storage

Abstract: Metabolic conditions characterized by elevated free fatty acid concentrations in blood and follicular fluid are often associated with impaired female fertility. Especially elevated saturated fatty acid levels can be lipotoxic for several somatic cell types. The aim of this study was to determine the impact of elevated free fatty acid concentrations in follicular fluid on neutral lipids (fatty acids stored in lipid droplets) inside cumulus cells and oocytes and their developmental competence. To this end, cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 59 publications
6
160
1
2
Order By: Relevance
“…Heifers with moderate body condition score had less fatty acids in aspirated COCs than heifers with low body condition score; and the inclusion of a lipid supplement in the diet for 35 days increased the total fatty acid content of whole COCs (Adamiak et al 2006). In contrast to experiments that increased or altered fat in the diet, cows that were fasted for 4 days also exhibited increased NEFA in both plasma and follicular fluid (Jorritsma et al 2003, Aardema et al 2013. Interestingly, there are also seasonal changes in the fatty acid composition of bovine ovarian follicles.…”
Section: Diet and Body Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…Heifers with moderate body condition score had less fatty acids in aspirated COCs than heifers with low body condition score; and the inclusion of a lipid supplement in the diet for 35 days increased the total fatty acid content of whole COCs (Adamiak et al 2006). In contrast to experiments that increased or altered fat in the diet, cows that were fasted for 4 days also exhibited increased NEFA in both plasma and follicular fluid (Jorritsma et al 2003, Aardema et al 2013. Interestingly, there are also seasonal changes in the fatty acid composition of bovine ovarian follicles.…”
Section: Diet and Body Compositionmentioning
confidence: 96%
“…increased oocyte droplet size and number (Aardema et al 2011). However, when bovine COCs were treated with a mixture of these three NEFAs (palmitic/stearic/ oleic acids) during IVM, oocyte lipid content was not affected even though cumulus cells exhibited lipid accumulation (Aardema et al 2013). Addition of conjugated linoleic acid (t10,c12CLA) to bovine COCs during maturation increased t10,c12CLA content in both cumulus cells and oocytes, but did not alter total fatty acid levels (Lapa et al 2011).…”
Section: Effects Of Lipid Supplementation During Oocyte Ivmmentioning
confidence: 99%
“…Furthermore, higher total lipid levels, and in particular TAG presenting acylation with oleic and palmitic acids, are observed in cumulus-enclosed than in denuded oocytes (5). Stored neutral lipids may be very important energy sources to be used through β-oxidation as well as precursors for de novo membrane synthesis during embryo development (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the composition and balance of saturated and unsaturated NEFAs in follicular fluid may distinctly modify these potential toxic effects of NEFAs on oocyte developmental competence. As recently demonstrated both in vivo and in vitro, exposure of maturing oocytes to elevated NEFAs can affect either β-oxidation or lipogenesis, crucial mechanisms for postfertilization developmental competence (4,5).…”
Section: Introductionmentioning
confidence: 96%
“…The same laboratory suggests that these negative effects of NEFAs on the embryo could be a consequence of modified energy metabolism and particularly, mitochondrial β-oxidation of fatty acids in the oocyte (Van Hoeck et al, 2013). A recent study has shown that bovine cumulus cells are able to protect maturing oocytes from potential harmful effects of increased local concentrations of fatty acids by intracellular storage of lipids (Aardema et al, 2013).…”
Section: Nefasmentioning
confidence: 99%